Hemostasis Laboratory Diagnostics: Characteristics, Communication Issues, and Current Challenges Resulting from Centralization of Laboratory Medicine - Scharf, Rüdiger E. (Hämostaseologie, 2020)
Laboratory diagnostics of patients with bleeding and thrombotic disorders can be a delicate task, which requires special skills and expertise. In this article, characteristic features of hemostasis testing are reviewed, including staged protocols and synoptic assessment of the patient history, clinical symptoms, and laboratory findings. Despite major progress in the diagnostic and therapeutic management, centralized testing of hemostasis can be associated with substantial challenges, resulting from the current dissociation between the clinical and laboratory world. To address some of these challenges, possible solutions are discussed, including adaptation of an established working paradigm.
Keywords: laboratory testing; hemostasis; diagnostic algorithms; quality control; communication